2011
DOI: 10.4018/jthi.2011040103
|View full text |Cite
|
Sign up to set email alerts
|

ICT Integration in Nigeria

Abstract: In the past few decades, there has been a lineal relationship between technology and development- the belief that availability of technology would produce development. This is evident in the advancements in Information and Communication Technologies (ICT), together with their rapid application in all spheres of mankind’s life that have led many to call our society ‘the information society’. It has become an important tool of governance that should be employed by every country-a tool Nigeria has failed to apply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…However, the non-domestication of an international treaty does not detract from the obligation Nigeria has undertaken under that instruments in respect of other nations in international law as long as Nigeria is a signatory to that instrument and have ratified or acceded to the treaty as the case may be (s.27 Vienna Convention on the Law of Treaties 1969). In Treatment of Polish Nationals and Other Persons of Polish Origin or Speech in the Danzig Territory (1932) the Permanent Court of International Justice in its advisory opinion stated "it should, however, be observed that a state cannot adduce as against another State its own constitution with a view to evading obligations incumbent upon it under international or treaties in force" (Eke, 2020). Nwande (2017: 18) distinguished between a nation's domesticated rights and every other right, which a nation has not recognized as follows:…”
Section: Incorporation Of Ihrl Into Nigerian Domestic Lawmentioning
confidence: 99%
“…However, the non-domestication of an international treaty does not detract from the obligation Nigeria has undertaken under that instruments in respect of other nations in international law as long as Nigeria is a signatory to that instrument and have ratified or acceded to the treaty as the case may be (s.27 Vienna Convention on the Law of Treaties 1969). In Treatment of Polish Nationals and Other Persons of Polish Origin or Speech in the Danzig Territory (1932) the Permanent Court of International Justice in its advisory opinion stated "it should, however, be observed that a state cannot adduce as against another State its own constitution with a view to evading obligations incumbent upon it under international or treaties in force" (Eke, 2020). Nwande (2017: 18) distinguished between a nation's domesticated rights and every other right, which a nation has not recognized as follows:…”
Section: Incorporation Of Ihrl Into Nigerian Domestic Lawmentioning
confidence: 99%
“…The digital divide is defined as the unequal access and usage of ICT worldwide (Eke, 2011). In the least-developed countries, the lack of physical access (insufficient network coverage) and material access are the primary factors that create the digital divide.…”
Section: Disabled People and The Digital Dividementioning
confidence: 99%